Dynamic of girl students’ psycho-physiological indicators in process of their study at pedagogical higher educational establishment - A.N. Kolumbet (Physical Education of Students, 2016)
Purpose: to study dynamic of psycho-physiological indicators of pedagogic higher educational establishments’ girl students. Material: in the research 510 girl students participated. We assessed: responsive abilities, static and dynamic balance, orientation in space, quickness of operational thinking, volume of rote memorization, distribution of attention, accuracy level, quickness and re-switching of attention, accuracy of fulfillment of task. Results: we have found weakening of accuracy of movement’s amplitude and pre-set value of force reproduction; reduction of indicators of response to vertically falling object, static and dynamic balance. We also registered improvement of indicators of nervous processes’ dynamic and ability to constructive praxis. Conclusions: uneven reduction of most of psycho-physiological indicators negatively reflects in girl students’ motor fitness level and professional abilities.